The Symbiosis Between Lactobacillus acidophilus and Inulin: Metabolic Benefits in an Obese Murine Model - Rangel Torres, Brian Eduardo; Rodriguez-Tadeo, Alejandra; Jimenez Vega, Florinda; Garcia Montoya, Isui Abril (2022)
Obesity is defined as having an excess of adipose tissue and is associated with the development of diabetes, hypertension, and atherosclerosis, which are the main causes of death worldwide. Research shows that probiotics and prebiotics reduce the metabolic alterations caused by high-fat diets. Therefore, this work evaluated the effect of the incorporation of Lactobacillus acidophilus (probiotic) and inulin (prebiotic) in the diet through obesity markers (biochemical, anthropometric, and molecular markers) in an obese murine model. Four treatments were administered: (1) hypocaloric diet (HD), (2) HD + L. acidophilus, (3) HD + inulin, and (4) DH supplemented with L. acidophilus + inulin for 8 weeks. After treatment, glucose, triglycerides, total cholesterol, HDL-C, and LDL-C in plasma were determined. In addition, the total body weight and adipose tissue were taken to calculate the body mass index. Following RNA extraction from adipose tissue, the expression of PPAR gamma, PPAR alpha, and transforming growth factor beta 1 (TGF1β) was evaluated by semiquantitative PCR. All treatments showed an improvement in biochemical markers compared to the values of the obese model (p < 0.05). Optimal values for blood glucose (133.2 ± 14.3 mg/dL), triglycerides (71 ± 4.6 mg/dL), total cholesterol (48.9 ± 6 mg/dL), HDL-C (40.9 ± 4.8 mg/dL), and LDL-C (8.4 ± 1.7 mg/dL) were obtained in the mixed treatment. Regarding fat mass index (FMI), prebiotic treatment caused the greatest reduction. On the other hand, mixed treatment increased the gene expression of PPARα and TGF1β in adipose tissue with DH with L. acidophilus and inulin treatment. This work demonstrates that the use of L. acidophilus and inulin as a complementary treatment is a viable alternative for prevention and action as a complementary treatment for obesity given the reduction in biochemical parameters and anthropometric indices; these reductions were greater than those found in the classic treatment of obesity due to the induction of the expression of genes related to lipid metabolism and anti-inflammatory cytokines, which contribute to reducing the high levels of glucose, triglycerides, and cholesterol caused by obesity.